2020
DOI: 10.1101/2020.01.13.904284
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensory and Behavioral Components of Neocortical Signal Flow in Discrimination Tasks with Short-term Memory

Abstract: In neocortex, each sensory modality engages distinct primary and secondary areas that route information further to association areas. Where signal flow may converge for maintaining information in short-term memory and how behavior may influence signal routing remain open questions. Using wide-field calcium imaging, we compared cortexwide neuronal activity in layer 2/3 for mice trained in auditory and whisker-based tactile discrimination tasks with delayed response. In both tasks, mice were either active or pas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 91 publications
1
23
0
Order By: Relevance
“…RL receives more than 20% of its connectional input from the barrel field, versus only 12.3% for AM and 2% for MMA. This observation is being backed up by recent imaging studies that observed activity in RL upon tactile engagement (Gallero-Salas et al, 2020;Olcese et al, 2013). Although we did not observe a notable difference in the amount of neurons projecting from V1, it has recently been put forward that RL receives the most projections from V1, compared to AM or MMA (Froudarakis et al, 2019).…”
Section: Rl Am and Mma Have Distinct Connectional Patternssupporting
confidence: 65%
See 1 more Smart Citation
“…RL receives more than 20% of its connectional input from the barrel field, versus only 12.3% for AM and 2% for MMA. This observation is being backed up by recent imaging studies that observed activity in RL upon tactile engagement (Gallero-Salas et al, 2020;Olcese et al, 2013). Although we did not observe a notable difference in the amount of neurons projecting from V1, it has recently been put forward that RL receives the most projections from V1, compared to AM or MMA (Froudarakis et al, 2019).…”
Section: Rl Am and Mma Have Distinct Connectional Patternssupporting
confidence: 65%
“…Most of the functional information about RL, AM and MMA comes from studies focused on investigating their visual field coverage or spatial and temporal frequency preferences (Han et al, 2018;Marshel et al, 2011;Zhuang et al, 2017). A couple of recent studies do show that RL gets input from not only visual, but also auditory and somatosensory areas (Gallero-Salas et al, 2020;Olcese et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the third section, we use murine data collected in both rest and task states to map levels of anisotropy across different cortical regions directly via the in vivo timeseries. These wide-field calcium imaging data were collected across the left hemisphere of mouse cortex expressing GCaMP6f in layer 2/3 excitatory neurons (Fagerholm et al, 2021;Gallero-Salas et al, 2021;Gilad et al, 2018), with cortical areas aligned to the Allen Mouse Common Coordinate Framework (Mouse & Coordinate, 2016),…”
Section: Overviewmentioning
confidence: 99%
“…All animal experiments were carried out according to the guidelines of the Veterinary Office of Switzerland following approval by the Cantonal Veterinary Office in Zürich. All murine calcium imaging data were collected as previously reported (Fagerholm et al, 2021;Gallero-Salas et al, 2021;Gilad et al, 2018). As with the synthetic data, we perform Bayesian model inversion to obtain posterior estimates for the parameter quantifying the extent to which the time series for each pixel deviate from isotropy at = 0 .…”
Section: Empirical Datamentioning
confidence: 99%
“…For example, goaldirected perceptual tasks require computations engaging various regions, including sensory, motor, memory, and reward circuits to generate complex apt behaviors (1, 2). Recent advances in electrophysiological (3) and optical methods (4) enabled direct measurements of large-scale neuronal activity distributed across multiple regions of the mouse brain in visual (1, 5), tactile (6), auditory (5,6), and olfactory (7) discrimination tasks. These studies revealed that activity in many regions represented task-related behavioral variables once expert performance is reached, indicating distributed and parallel sensorimotor processing.…”
mentioning
confidence: 99%